Effect of Cash Turnover On Liquidity at PT. Pekebun Nusantara VIII Of Sukabumi 2013 - 2017: Manajemen Keuangan - ENDANG NARYONO, SE., MM (P3M STIE PASIM Sukabumi, 2020)
Research aims to understand gyrations cash pt .Had provided nusantara viii , liquidity to pt .Had provided nusantara viii , and to know the influence of gyrations cash on the level of liquidity to PT .Perkebunan nusantara VIII sukabumi .The methodology used is the method ex-post facto capital .This research using primary and secondary data obtained from financial reports and non financial from pt .Pekebunan nusantara viii sukabumi .To test hypotheses used linear regression and the correlation with on the spss 15.0 for windows.Based on the results of research shows that there is a positive influence between second match of cash and liquidity pt .Had provided nusantara viii sukabumi .A level of closeness ( correlation ) the second variables strong enough , are r = 0,800 with a value of a correlation coefficient r & gt; 0 it means if cash second match of getting up and liquidity will increase , and vice versa . While from the results of the equation above the results linear regression simple as follows: y = 185,137 + 0,045x means value ( a ) or constant of 185,137 who have the meaning that if cash two zero ( 0 ) or not increased so level of 185,137 liquidity .The score regression ( b ) of 0,045 the show the relation in line that every 1 increase point in cash and two rate rose to 185,137 liquidity